Complications associated with the use of hyaluronic acid and their management - a literature review - Turczynowicz, Magda; Lewandowska, Karina; Janikowski, Wojciech; Jóźwicka, Agnieszka; Radwańska, Natalia; Górska, Weronika; Król, Jerzy (Quality in Sport, 2025)
Introduction: Aesthetic medicine is a rapidly growing field, as evidenced by statistics from the American Society of Plastic Surgeons. Like any medical procedure, treatments with hyaluronic acid (HA) fillers carry a risk of complications or adverse effects. These complications can be broadly categorized into non-vascular and vascular events. Non-vascular complications include nodules, granulomas, oedema, Tyndall effect, infections, and biofilm formation. Vascular complications encompass ischemia, necrosis, and severe outcomes such as blindness or other visual impairments. Purpose: This study aims to compile and analyze current data on HA filler treatments and their associated complications within the scope of aesthetic dermatology. Materials and Methods: A comprehensive manual review of scientific databases, including Scopus, EMBASE, and Medline, was conducted for articles published up to November 2024. Summary: This review underscores the spectrum of complications related to HA fillers, emphasizing the importance of prevention, early diagnosis, and appropriate management. Although HA fillers are generally regarded as safe, the potential for complications persists. This reinforces the necessity of meticulous preparation, adherence to established guidelines, and continuous education for clinicians. Such measures can significantly minimize the incidence and severity of adverse events, thereby improving patient outcomes.